Efektivitas E-Purchasing terhadap Pembelian Produk Dalam Negeri di Biro Pengadaan Barang dan Jasa Provinsi Sumatera Utara - Hutasuhut, Syafrial Aulia; Revida, Erika; Nasution, Muhammad Arifin (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study examines the effectiveness of e-purchasing in promoting domestic product utilization within the Bureau of Goods and Services Procurement of North Sumatra Province and explores the barriers affecting policy implementation. Using a qualitative descriptive case study, data were obtained through document review, observation, and interviews with procurement officials and stakeholders. Findings show that e-purchasing has improved efficiency and transparency in procurement and encouraged greater use of domestic products, although outcomes remain limited. While there is a positive trend in procurement packages meeting the Domestic Component Level (TKDN), the proportion remains relatively low. Key barriers include the weak competitiveness of local products, limited user understanding of the e-purchasing system, and inadequate oversight of TKDN enforcement. The study recommends strengthening local business capacity, expanding policy dissemination, and improving monitoring mechanisms to enhance the role of e-purchasing in supporting economic self-reliance through domestic products.‎